German and international crisis management in the Sahel: Why discussions about Sahel policy are going around in circles - Denis Tull (Stiftung Wissenschaft und Politik (SWP), 2020)
In May, Germany's parliament approved the country's continued military participation in two missions in Mali and the Sahel. As part of the UN Multidimensional Integrated Stabilization Mission (MINUSMA) and the EU Training Mission EUTM Mali, up to 1,550 German soldiers can be deployed. Given the scale of these engagements, which are currently Germany's largest, German discussions on Sahel policy, like those elsewhere, have been sluggish and unproductive. One reason for this is that buzzwords and false certainties determine the debate, which is largely detached from strategic considerations.
Keywords: 320